CNS symptoms in myotonic dystrophy type 1 (DM1): report of three cases - Jara-Velásquez, Celia (2025)
Myotonic dystrophy type 1 is an autosomal dominant hereditary neuromuscular disorder with systemic manifestations. It is characterized by progressive muscle weakness, myotonia, and cataracts, alongside variable involvement of the cardiovascular, endocrine, and central nervous systems. This report highlights three cases of myotonic dystrophy type 1 with significant central nervous system involvement, presenting with structural changes in brain MRI, cognitive decline, epilepsy, and behavioral changes. These cases underscore the importance of a multidisciplinary evaluation, including neuropsychiatric assessments and neuroimaging studies, as an integral part of the comprehensive management of these patients.